Enhanced Integer-Based Homomorphic Encryption Scheme with Windowing Mechanism for Securing Electronic Health Records - Jalal, Abdulrahman Tawfeeq; Mohammed, Mohammed Anwar (UHD Journal of Science and Technology, 2025)
The frequent breaches of healthcare data annually make robust encryption mechanisms crucial, especially those that preserve the usefulness of the data while ensuring privacy. This study addresses specific integer-based homomorphic encryption systems and their critical vulnerabilities. The vulnerability identified in these systems is the possibility of decryption using other values, such as factors or primes, instead of the claimed unique secret key. We propose an enhanced cryptographic formula to address this vulnerability using a double random value technique that ensures decryption depends solely on the designated secret key. We also apply a windowing technique for prime selection to enhance the key properties against pattern detection attacks. Security analysis shows that the enhanced system prevents decryption using values other than the dedicated key while maintaining additive and multiplicative homomorphism. Performance evaluations show that the improved system maintains decryption times and ciphertext expansion ratios similar to the original system, with a reasonable decryption time reduction. Statistical testing results using the National Institute of Standards and Technology tests demonstrate the robustness of the proposed approach compared to the original, with the windowing technique exhibiting superior randomness properties.